Asam Salisilat sebagai Penginduksi Ketahanan Tanaman Padi terhadap Penyakit Hawar Daun Bakteri - Christoffol Leiwakabessy; Meity Suradji Sinaga; Kikin Hamzah Mutaqin; Trikoesoemaningtyas Trikoesoemaningtyas; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2017)
The use of salicylic acid as resistance inducers agents in several plants species was well known. Salicylic acid has been believed to play an important role in inducing resistance against some pathogen. This research was aimed to study the role and effectiveness of salicylic acid as inducers for the resistance of some rice variety against bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae. The experiment was arranged in completely randomized factorial design with three factors i.e. rice variety, salicylic acid, and pathotypes, each treatment was replicated three times. The results showed that salicylic acid could prolong the latent period of X. oryzae pv. oryzae pathotypes IV and VIII in paddy rice varieties Conde and Ciherang,  induce the resistance of rice varieties as well as reducing the rate of infection of the two mentioned pathotypes. Salicylic acid was also able to induce the resistance of Conde and Ciherang varieties in order to suppress area under disease progress curve (AUDPC)  of X. oryzae pv. oryzae pathotypes IV and VIII.